2020
DOI: 10.1039/d0gc00852d
|View full text |Cite
|
Sign up to set email alerts
|

Flexible polyurethanes, renewable fuels, and flavorings from a microalgae oil waste stream

Abstract: To achieve sustainably-sourced polymers from algae, azelaic acid was prepared from an algae oil waste stream and converted into a flexible polyurethane foam. The heptanoic acid co-product was converted into both a flavoring and a renewable solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 61 publications
0
25
0
2
Order By: Relevance
“… 26 , 48 Our ozonolysis studies in aqueous methanol suggested that polar organic solvents miscible in water improved the water nucleophilicity for carbonyl oxides, resulting in the direct formation of aldehydes, 26 avoiding the formation of energetic intermediates, 48 , 49 which are further oxidized with sodium chlorite to produce the desired carboxylic acid in high yield and purity. 18 , 24 However, our attempts to scale up these reactions faced several challenges.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 48 Our ozonolysis studies in aqueous methanol suggested that polar organic solvents miscible in water improved the water nucleophilicity for carbonyl oxides, resulting in the direct formation of aldehydes, 26 avoiding the formation of energetic intermediates, 48 , 49 which are further oxidized with sodium chlorite to produce the desired carboxylic acid in high yield and purity. 18 , 24 However, our attempts to scale up these reactions faced several challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Linear polyesters from oleic acid-based monomers were prepared and later converted into polyurethanes [88]. Polyesters prepared from microalgae oil lipids have also been described [90].…”
Section: Linear Polymers Based On Fatty Acids or Their Ensuing Derivativesmentioning
confidence: 99%
“…In a sustainable biorefinery approach, omega-3 fatty acids can be separated from microalgal lipids, while the rest of the lipid or other components of the biomass could be used for making food, fuel, or other valuables. For example, after the separation of omega-3 fatty acids from Nannochloropsis salina oil, the waste oils were used to produce flexible polyurethane foam (Phung Hai et al, 2020). This biodegradable polyurethane foam is an alternative to petroleum-based polymer and showed its application in making footwear and surfboard.…”
Section: Polyunsaturated Fatty Acidmentioning
confidence: 99%